The concept of rare book in the XVIII century. The reception of David Clement´s work in Spain - Varela-Orol, Concha (Revista General de Información y Documentación, 2016)
The concept of rare book is studied during the XVIII century starting from both, the main repertoires devoted to this subject in this period of time and the different positions that bibliographers and booksellers show about it. Taking as significant the reading that Martin Sarmiento makes of David Clement's work, it can be deduced that what both groups think about this kind of books show a great number of points in common, although the erudite circles pay a greater attention to the interest of the text and the value of the books to develop a history of learning in which rare books became fundamental written sources.
Keywords: Rare book; History of learning; Bibliography; Bibliophile; XVIII century; Martín Sarmiento; David Clément.